Large comprehensive evaluation of new- vs. old-generation ACURATE neo self-expanding valve during TAVI procedures: a decrease in paravalvular leakage with an increase in post-procedural gradients?. (3rd October 2022) - Karameh, H; Harari, E; Almagor, Y; Jubeh, R; Shuvy, M; Hellou, E; Taha, L; Butnaru, A; Wolak, A; Glikson, M; Dvir, D
Abstract: Background: Contemporary data comparing new- versus old-generation transcatheter heart valve (THV) devices are lacking regarding several THV devices. We aimed to compare the safety and efficacy of old-generation device (OGD) ACURATE neoTM versus the newer generation device (NGD) ACURATE neo2TM THVs (Boston Scientific) in patients undergoing transcatheter aortic valve implantation (TAVI). Methods: An analysis of patients undergoing transfemoral TAVI with old-generation device ACURATE neoTM versus newer generation device ACURATE neo2TM from 2016 to 2021. The primary end-point was early safety events at 30-days post-valve implantation. Significant post-implantation paravalvular leakage (PVL) was considered as ≥moderate. Results: A total of 249 patients were included in the evaluation; mean age was 81±7.2, and 95 (38.2%) were males. Of the total population 87 (35%) underwent TAVI with the NGD. Early safety events occurred in 21.8% NGD versus 19.1% in OGD (RR= 0.67, P=0.13). Permanent pacemakers were implanted within 30 days in 4.6% versus 6.2% in NGD versus OGD respectively (RR=1.343, P=0.77). Major vascular complications occurred in 5.7% in NGD versus 9.4% in OGD 9.4% (RR=1.6, P=0.46). More than mild PVL occurred significantly more often in OGD (P<0.0001). Echocardiographic mean gradient post-procedure was 9 mmHg± 5 in OGD versus 11±4 mmHg in the NGD (P=0.0159). Conclusion: New-generation ACURATE neo2TM devices were associated with less significant PVL. However, this new generation valve was also associated with higher residual gradients. This trend of decrease in PVL with an increase in gradients will be further studied. Funding Acknowledgement: Type of funding sources: None.